The appeal [compact disc, unabridged] - Grisham, John (Random House Audio, 2008)
Wall street millionaire Carl Trudeau purchases an unsuspecting candidate to run for Supreme Court judge when Mississippi rules against one of his chemical companies for dumping toxic waste into the towns water supply causing a cancer cluster.